Upaya Meningkatkan Hasil Belajar Siswa dalam Pembelajaran PAI & BP Menggunakan Model Pembelajaran Learning Together pada Siswa Kelas XI Farmasi di SMK Kesehatan Prima Nusantara Bukittinggi - Jefri Gunawan; Nofrizal Tanjung (Kampus Akademik Publiser, 2024)
This study originated from problems in PAI & BP learning in the 11th grade Pharmacy class at SMK Kesehatan Prima Nusantara Bukittinggi, where most students had difficulty understanding the learning material, resulting in low learning outcomes. Therefore, to improve student learning outcomes in PAI & BP learning, the Learning Together learning model was applied to 11th grade Pharmacy students at SMK Kesehatan Prima Nusantara Bukittinggi. This research is classroom action research using a qualitative approach. This research was conducted on students in the 11th grade Pharmacy class at SMK Kesehatan Prima Nusantara Bukittinggi. The instruments used to collect data were observation sheets, documentation, and learning outcome tests. The data obtained in the research was analyzed using qualitative and quantitative data analysis. This research was conducted in two cycles, with each cycle consisting of one meeting. The results of each cycle conducted using the Learning Together model show an improvement in both the learning process and student learning outcomes. This can be seen from the students' achievements in learning, where in cycle I the average score obtained by students only reached 60% with an average score of 68.48, while in cycle II there was a significant increase with an achievement rate of 84% and an average score of 80. Thus, it can be concluded that the use of the Learning Together model can improve student learning outcomes in PAI & BP XI Pharmacy at SMK Kesehatan Prima Nusantara Bukittinggi.